METODE PEMBELAJARAN TAJWIDDALAM MENINGKATKAN KEMAMPUAN MEMBACA AL-QUR'AN DI PONDOK PESANTREN SA’ADATUDDAREN JAMBI - M. Rayhan AL-Munawar; Ali Musa Lubis (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The ability to read the Quran correctly according to Tajwid rules is an essential competency for every Muslim, especially students in Islamic boarding schools. However, in reality, there are still many problems in mastering Tajwid, such as errors in makhraj (articulation points), letter characteristics, and the application of recitation rules. This study aims to describe the Tajwid learning methods applied at the Sa'adatuddaren Islamic Boarding School in Jambi, identify the difficulties faced by students, analyze supporting and inhibiting factors, and formulate innovative learning strategy recommendations to improve the quality of Quranic recitation. This research uses a descriptive qualitative approach with data collection techniques through observation, in-depth interviews with class VII/VIII students and Tajwid teachers, and document studies. Data were analyzed interactively through data reduction, presentation, and verification using triangulation techniques to ensure the validity of the findings. The results show that Tajwid learning methods in this boarding school are still dominated by conventional approaches such as talqin-taqlid (imitation) and lectures, with limited use of media and variety in techniques. Students face main difficulties in mastering letter articulation points, rules of nun sukun/tanwin, mim sukun, and the application of mad (prolongation). Inhibiting factors include students’ diverse educational backgrounds, low learning motivation, limited facilities, and lack of intensive mentoring. As a recommendation, this study proposes simplifying the material, increasing practical exercises (drills), utilizing audiovisual media, and providing more personalized and needs-based learning mentoring. Keywords : Learning Methods, Tajwid Science, Quran Reading Ability, Islamic Boarding School, Innovative Learning.